Female attitudes towards the idea of co-participation in the costs of hospital treatment - Łepecka-Klusek, Celina; Pilewska-Kozak, Anna B.; Kołodziejczyk, Tomasz; Pilewski, Bartosz D.; Jakiel, Grzegorz (Polish Journal of Public Health, 2011)
Introduction. The idea of patients’ co-participation in the costs of medical care services first appeared when the authorities began to reform the system of medical care.Aim. The purpose of the study was to investigate the attitudes of women undergoing gynecological operations towards the idea of co-participation in the costs of hospital treatment and to find out what part of money allocated for summer holidays they would be ready to spend on treatment.Material and methods. In total 272 women, who underwent elective gynecological operation within two months in 2008 were surveyed. The women were asked to fill in a specially developed questionnaire on the second day following the operation. First, the questionnaire was verified by pilot study in the group of 25 women; their results were excluded from final scores.Results. The results confirmed found that the respondents who had higher education supported the idea of co-participation in covering the costs of treatment more often (p=0.002), living in big cities (p=0.04), married (p=0.02), employed (p=0.01) and in better economic situation (p=0.001). The age turned out to be insignificant (p=0.09). The respondents reported that they were ready to use all that money to co-participate in the costs of hospital treatment - 148 women (54.4%); 34 (12.5%) respondents would use half the money for that; 74 (27.2%) women were unable to take decision and 16 (5.9%) would definitely not use that money for that. Variables assumed in the study, apart from living place, marital status and subjective perception of social conditions significantly differentiated the frequency of these statements.Conclusions. Women’s attitudes towards co-participation in the costs of hospital treatment vary and significantly correlate with education, place of living, professional and family status aside their economic situation. The fact that women are ready to resign from the money allocated for annual leave to co-participate in the costs of hospital treatment depends on their age, level of education, professional and family status and medical indication for surgery.